Can local ablative techniques replace surgery for locally advanced pancreatic cancer? - Heger, Ulrike; Hackert, Thilo (Journal of gastrointestinal oncology, 2021)
In the treatment of pancreatic ductal adenocarcinoma (PDAC) the best chance at long term survival or cure has to date always included the complete surgical removal of the tumor. However, locally advanced pancreatic cancer (LAPC), about 25% of all newly diagnosed PDAC, is defined by its primary technical unresectability due to infiltration of visceral arteries and absence of metastasis. Induction therapies, especially FOLFIRINOX treatment, together with technical surgical advancement have increased the numbers for conversion to secondary resectability. Recent data on resections after induction therapy show promising, almost doubled survival compared to palliative treatment. Yet, around 70% of LAPC remain unresectable after induction therapy, often due to persistent local invasion. As locally ablative techniques are becoming more widely available this review examines their possible applicability to substitute for surgery in these cases which we propose to group under the new term “Inconvertible LAPC”. The need for defining this novel subgroup who might benefit from ablative treatment is based on the findings in our review that high-level evidence on ablative techniques for PDAC is largely lacking and the latest effective, harmonized treatment guidelines for LAPC are not often incorporated in these studies. The “inconvertible LAPC” label requires persistent unresectability after staging and induction therapy of LAPC according to current guidelines followed by liberal indication for aggressive surgical exploration at a center equipped for extended pancreatic resections. Ideally, this specification of a new, distinct patient group will also put it in the spotlight more, hopefully prompt more trials designed to generate robust evidence and optimize transferability of study results.